Insoluble π‐Conjugated Polyimine as an Organic Adsorbent for Group 10 Metal Ions. Issue 17 (22nd March 2021) - Shirakura, Hayato; Hijikata, Yuh; Pirillo, Jenny; Yoneda, Tomoki; Manabe, Yumehiro; Murugavel, Muthuchamy; Ide, Yuki; Inokuma, Yasuhide
Abstract: Metal ion adsorbents are indispensable materials for the recovery of noble metal ions in a sustainable society. Herein, we report that poly(isopyrazole‐3, 5‐diyl‐ trans ‐vinylene) (1 ) effectively adsorbed group 10 metal ions from solution in acetonitrile. Owing to its fully π‐conjugated and rigid structure, polyimine 1 was virtually insoluble in common organic solvents and water, making it advantageous for metal ion adsorption via a solid/liquid interface. Inductively coupled plasma (ICP) analysis showed that ≥90 % of Ni 2+, Pd 2+, and Pt 2+ ions were adsorbed at a concentration of 10 μM (order of ≤2 ppm) after stirring suspensions at room temperature. Metal ion desorption was achieved by treatment with ethylenediaminetetraacetic acid disodium salt (EDTA ⋅ 2Na), and the adsorbent was reused. Theoretical calculations supported that the desolvation energy was an important factor for effective adsorption in acetonitrile. Abstract : Insoluble organic metal ion adsorbent, poly(isopyrazole‐3, 5‐diyl‐ trans ‐vinylene), was generated from a soluble polyketone precursor by post‐synthetic functionalization, including quantitative imination and a solubility change upon π‐conjugation formation. This material adsorbed more than 90 % of group 10 metal ions (Ni 2+, Pd 2+, and Pt 2+ ) from their dilute acetonitrile solutions (≤2 ppm).